UKURAN LINEAR TUBUH DAN BERAT BADAN TERNAK BABI MENURUT JENIS KELAMIN PADA KEMITRAAN PROPOSIONAL DI KELOMPOK TANI SYALOM TUATUKA - Arnold C. Tabun; Melkianus D.S. Randu; Max A. Supit; Thomas Lapenangga; Cardial L. O. Leo Penu; Johanis Jermias (Partner, 2018)
Proportional Partnership Format of Animal Husbandry Department of Kupang State Agricultural Polytechnic is be applied in pigs fattening in order to improve feed management and maintenance of pigs at Syaloom Farmers Group in Tuatuka Kelurahan of East Kupang. This experiment aims to determine the effect(s) of Poliagro complete feed on linear body sizes (body length, chest circumference, height) and daily body weight gain between female and male pigs. Experimental farm method was used in the experiment in which 10 pigs are used (consist of 3 males and 7 females).Data was analysis using descriptive statistics and t-student test to compare variables of both groups by using IBM-SPSS software version 21. The results showed that after 5 months, the average linear sizes of male group (body length, chest circumference and height) were 29.33 ± 0.57; 77.67 ± 2.51 and 94.33 ± 4.04in sequentially order. While the linear sizes of the female pig's were 27.67 ± 1.53; 75.67 ± 3.21and 90.67 ± 1.52. The mean of daily weight gain of male pigs was 0.49 ± 0.01 kg/head/day and the females ones 0.46 ± 0.02 kg/head/day. Statistical analysis showed that there were no differences in linear body sizes and daily body weight gain between male and female pigs that were fed Poliagro pellet fee.